Combination of Four Serum Exosomal MiRNAs as Novel Diagnostic Biomarkers for Early-Stage Gastric Cancer - Tang, Shuli; Cheng, Jianan; Yao, Yuanfei; Lou, Changjie; Wang, Liang; Huang, Xiaoyi; Zhang, Yanqiao (Frontiers in Genetics, 2020)
Gastric cancer (GC) remains a leading cause of cancer-related mortality in the United States and China, there is an urgent need to discover novel non-invasive biomarkers for the early diagnosis of GC to improve the prognosis of GC patients. Exosomal miRNAs are considered promising biomarkers for cancer diagnosis. Using next-generation sequencing (NGS), bioinformatics and further validation, we identified and evaluated exosomal miRNAs in serum as early diagnostic markers for GC. NGS revealed that the average mappable reads in the RNA libraries were about 6.5 million per patient inluding miRNAs (73.38%), rRNAs (17.10%), snRNAs (8.83%), snoRNAs (0.65%), and tRNAs (0.04%). A total of 66 up and 13 down-regulated exosomal miRNAs were found in the screened cohort. In the validation cohort, by comparing with healthy individuals, higher levels of serum exosomal miR-92b-3p, let-7g-5p, miR-146b-5p and miR-9-5p were found to be significantly associated with early-stage GC (p < 0.05). Diagnostic power of the combined panels of the exosomal miRNAs or the combination of exosomal miRNAs and CEA outperformed that of single exosomal miRNA marker for establishing a diagnosis of early-stage GC. The combined diagnosis of exosomal miR-92b-3p + let-7g-5p + miR-146b-5p + miR-9-5p with CEA had the most powerful efficiency with an AUC up to 0.786. In addition, serum levels of exosomal miR-92b-3p were significantly associated with poor cohesiveness (p = 0.0021), let-7g-5p and miR-146b-5p were significantly correlated with nerve infiltration (p = 0.0234 and p = 0.0126, respectively), and miR146b-5p was statistically correlated with tumor invasion depth in early-stage GC (p = 0.0089). In conclusions, serum exosomal miR-92b-3p, -146b-5p, -9-5p, and let-7g-5p may serve as potential noninvasive biomarkers for early diagnosis of GC.